Wrinkles in time - Smoot, George; Davidson, Keay. (New York : Avon Books, 1993)
Presents the discovery of wrinkles in the fabric of space-time by the COBE satellite in 1992 in text and photographs.
The dark night sky -- The expanding universe -- Cosmological conflict -- The inflationary universe.
Includes bibliographical references (p. 317-318) and index.
Adult
Adult
Wilson's Public Library
Library Journal Starred
Library Journal
Keywords: Cosmology; Cosmology; Universe